ENGLISH LISTENING TEST ITEMS EVALUATION: A CASE OF A TEACHER-MADE TEST OF SMK N 5 PONTIANAK 2014 - Lestari, Windy Ayu; Ikhsanudin, Ikhsanudin; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to evaluate and provide information about the quality of English listening test items. Evaluation a set of test items are to measure the content validity, the reliability, the level of difficulty, the discriminating power, and the distracters, for the first semester of grade twelve students in SMK N 5 Pontianak in Academic year 2013/2014. This research is an evaluation to a set of teacher-made test that consist of 15 multiple-choice test items. There are 31 studentsâ€™ in one class as the participant of the test. The data of this research were collected using a documentary technique. The data were taken from the result of an English listening summative test, English listening test paper, answer key, studentsâ€™ answer sheets, listening script, and test item specification. The finding of this research is the content of all of the test items is valid based on the test item specifications. However, based on the criteria used to classify the degree of reliability, the items are not reliable; the score is only 0.183 (negligible). Although the content of all of the test items is valid, the test items cannot be used continuously because it is not reliable, and the test items need several revision. Furthermore, the mean of items difficulty level has fulfilled the requirements of good test items in term of difficulty level with 0.688 (Moderate). The mean of discriminating power is 0.256 (moderate) that means it has fulfilled the requirements of good test items. There were 26 distracters that should be revised. Besides, there are 4 good test items which still can be used as reference for the next English summative test. There are 3 test items that should be discarded or changed by the other test items and 8 test items should be revised if the teacher wants to use the test for the next English summative test.Â Keywords: Item Analysis, Listening Test Items